Structure of 4-(1-phenyl-1-methylcyclobutyl-3-yl)-2-aminothiazole - Aksoy, Ilhan; Çukurovali, Alaaddin; Güven, Kutalmiş; Yilmaz, Ibrahim; Sari, U?ur (Japan Society for Analytical Chemistry, 2003)
The crystal structure of 4-(1-phenyl-1-methylcyclobutyl-3-yl)-2-aminothiazole (C14H16N2S) has been determined by X-ray - analysis. It crystallizes in the triclinic space group P1, with unit cell parameters: a = 10.4686(16), b = 11.9543(16), c = 5.9271(16)Å, ? = 102.365(16), ? = 92.120(16), ? = 65.302(15)o, V = 657.1(2)Å3, Dc = 1.235 g/cm3, and Z = 2. The crystal structure was solved by direct methods and refined by full-matrix least squares to a final R-value of 0.041 for 2561 observed reflections. In the thiazole ring, N2=C1 and C1-S1 bond distances are 1.304(2) and 1.7415(16)Å, respectively. 2003 © The Japan Society for Analytical Chemistry.